Pemanfaatan Limbah Botol Kaca Guna Meningkatkan Kreativitas Keluarga Yang Memiliki Nilai Ekonomis - Wardhani, Rachmasari Pramita (Journal of Community Service and Society Empowerment, 2024)
Waste or also known as rubbish is a problem that is quite complex for the government to handle, especially household waste which is never separated from the use of inorganic or organic materials every day. In maintaining a clean and comfortable environment, especially in the city, especially in Balikpapan, existing waste is separated at disposal. By referring to green environment principles, it is hoped that people will not throw rubbish or waste carelessly or at certain times. Referring to the problem of handling waste made from glass, in this case glass bottle waste, this article examines the use of glass bottle waste to increase family creativity which has economic value. The aim of writing community service is to: 1) Increase the community's sense of awareness in efforts to handle solid waste, in this case glass material waste. 2) Can provide information to the public about how to recycle glass waste. The type of method used is qualitative, document study and narrative in nature. There are various ways of recycling, in the study of community service writing it is how to disseminate useful information to society at the lowest level, namely households. Where waste management can begin to be implemented in the home and family environment, this can of course also be a motivation and build creativity in the skilled hands of children at home. where they can be given an understanding of how to create a clean and comfortable living environment, as well as foster creativity that creates added value that is beneficial from an economic perspective. Treatment for waste management starts from the smallest line, namely the family or household. The application of the go green concept with 3R can be applied in households in waste management, one of which is inorganic waste, namely glass bottles.